PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK BERBASIS QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK - Chantika Lina Heryanti; Rina Yuliana; Sigit Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
During the learning process, teachers do not modify their teaching methods enough and do not utilize creative, innovative, interactive, and engaging learning media. Consequently, students are less motivated and their cognitive learning outcomes in Indonesian subjects decline. Therefore, there needs to be learning media that supports the learning process. Therefore, researchers decided to use Quantum Teaching-based Flipbook media with the TANDUR method (grow, experience, name, demonstrate, repeat, and celebrate) in the learning process. This research and development aims to develop Quantum Teaching-based Flipbook media, especially in Indonesian subjects, namely the Sehatlah Ragaku material, to describe the feasibility level of Quantum Teaching-based Flipbook media developed to measure student understanding after using Quantum Teaching-based Flipbook media. Research this study was conducted at SDN Kragilan 6 in grade IV with 20 students consisting of 9 boys and 11 girls. The research method was R&D (Research and Development) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The validation results from the learning material experts from both validators obtained an average percentage of 90.5%, meeting the criteria of "Very Appropriate". The results of the validation of learning language experts from both validators got an average percentage of 87.5% with the criteria of "Very Appropriate. The results of the validation of media experts from both validators got an average percentage of 87.3% with the criteria of "Very Appropriate". The overall average percentage of validators got a percentage of 88% with the criteria of "Very Appropriate". The increase in understanding of cognitive learning outcomes of students got a percentage of 85.5% which is included in the category of "Very Good", as well as the average results of cognitive learning tests of 0.72 that the increase in the average value of students is included in the high category because N-gain is in the interval of N-gain> 0.7. If we pay attention to the results of the N-gain test, the increase in cognitive understanding in students after studying the material is already at a high level.